Zapomniane miasto, wieś i dwór Zwanowo. Przyczynek do badań nad późnośredniowiecznym i nowożytnym zespołem osadniczym w Niedźwiedzinach (przysiółek Dzwonowo), pow. wągrowiecki, woj. Wielkopolskie - Krzepkowski, Marcin; Moeglich, Marcin (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2014)
A Forgotten Town, the Village and Manor Zwanowo. Contribution to the Studies into Late Mediaeval and Modern Settlement Complex in Niedźwiedziny (Hamlet Dzwonowo), Administrative District Wągrowiec, Great Poland. The article presents a preliminary interpretation of vegetation dissimilarities recognized due to the analysis of an orthophotomap published on the Internet site www.geoportal.gov.pl. The dissimilarities in question, visible in the grounds of the village of Niedźwiedziny (hamlet Dzwonowo), administrative district Wągrowiec, Great Poland (Wielkopolska), have been construed as the remains of a unique mediaeval settlement complex: oval-shaped village, chartered town and a mediaeval (?) and modern manor. During visits to the abovementioned sites, the area of the old churchyard cemetery was traced. On the basis of the written sources, it has been established that Dzwonowo was the main centre of the joint properties owned by Dobrogost – Poznań voivode, and subsequently his descendants.